2008
DOI: 10.5194/bgd-5-2003-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Branch xylem density variations across Amazonia

Abstract: Abstract. Measurements of branch xylem density, Dx, were made for 1466 trees representing 503 species, sampled from 80 sites across the Amazon basin. Measured values ranged from 240 kg m−3 for a Brosimum parinarioides from Tapajos in West Pará, Brazil to 1130 kg m−3 for an Aiouea sp. from Caxiuana, Central Pará, Brazil. Analysis of variance showed significant differences in average Dx across the sample plots as well as significant differences between families, genera and species. A partitioning of the total va… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 76 publications
3
14
0
Order By: Relevance
“…2008). This result is concordant with recent Amazon‐wide estimates for tree xylem density, where local environmental factors explained up to 22% of variability in sapwood density (Patiño et al. 2009).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…2008). This result is concordant with recent Amazon‐wide estimates for tree xylem density, where local environmental factors explained up to 22% of variability in sapwood density (Patiño et al. 2009).…”
Section: Discussionsupporting
confidence: 90%
“…We chose the threshold values to provide the greatest discrimination among the sampling designs we simulated; the larger threshold for trait variance reflects the inherent variation in these plant functional traits (Wright et al. 2004; Patiño et al. 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In the Terra Firme forest (TFF), under both non-limiting and limiting soil water conditions (wet season/dry season), a large variability in stem CO 2 efflux was observed among trees (Table 3); the range of E s values was similar to previous observations made in tropical rainforest ecosystems (Cavaleri et al 2006;Chambers et al 2004;Meir and Grace 2002;Nepstad et al 2002;Ryan et al 1994;Zach et al 2008Zach et al , 2010b and confirmed the large variability in functional characteristics observed to date for Neotropical rainforest species at the stem level (e.g., wood density- Patiño et al 2008, bark thickness-Paine et al 2010. In a study on functional explanations for variation in bark thickness in Neotropical trees, Paine et al (2010) concluded there was no significant relationship between bark thickness and E s .…”
Section: Between-tree Variabilitysupporting
confidence: 87%
“…2004; ter Steege et al. 2006; Patiño et al. 2008), as does a positive but weaker relationship between wood density and temperature.…”
Section: Biogeography and Evolution Of Wood Traitsmentioning
confidence: 95%
“…Heartwood xylem lacks functional conduits and parenchyma. Foresters typically measure heartwood density, yet sapwood (xylem containing functional conduits and parenchyma) densities are often significantly lower than heartwood densities (Woodcock & Shier 2002;Patiño et al 2008). This pattern has been attributed to the structural support required at different ontogenetic stages or changes in chemical deposition in heartwood.…”
Section: A Wood Density As An Integrator Of Wood Propertiesmentioning
confidence: 99%